1990
DOI: 10.1002/ijc.2910450531
|View full text |Cite
|
Sign up to set email alerts
|

Monosialoganglioside biosynthesis by subcellular membranes of rhabdomyosarcoma cell lines differing in metastatic potential

Abstract: We found that rhabdomyosarcoma (RMS) subcellular membranes contain sialyltransferase activities for LcOse4Cer and GgOse4Cer acceptors. Chromatographic analyses and neuraminidase lability of the sialyltransferase products indicated that the principal site of sialylation was the non-reducing terminal galactosyl moiety. In order to control for the effects of cell density in culture, metastatic S4T18 RMS cells and nonmetastatic F9-4/21 RMS cells were harvested at 2 X 10(4) to 6 X 10(4) per cm2 prior to analyses. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Cardiac glycosides (CGs) (e.g., digitoxin, digoxin, ouabain, and oleandrin) are selective inhibitors of the Na + /K + -ATPase pump (NKA), , commonly used to treat heart failure ( Pavlovic, 2020 ). The aberrant expression/activity of NAK has been found in several cancer types ( Mijatovic et al, 2012 ; Durlacher et al, 2015 ), including RMS ( Liepkans, 1990 ). Thus, CGs have shown towards some types of malignant tumors, both in vitro and in vivo ( López-Lázaro et al, 2005 ; Kumavath et al, 2021 ), working at concentrations commonly found in the plasma of cardiopathic patients treated with CGs ( López-Lázaro et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac glycosides (CGs) (e.g., digitoxin, digoxin, ouabain, and oleandrin) are selective inhibitors of the Na + /K + -ATPase pump (NKA), , commonly used to treat heart failure ( Pavlovic, 2020 ). The aberrant expression/activity of NAK has been found in several cancer types ( Mijatovic et al, 2012 ; Durlacher et al, 2015 ), including RMS ( Liepkans, 1990 ). Thus, CGs have shown towards some types of malignant tumors, both in vitro and in vivo ( López-Lázaro et al, 2005 ; Kumavath et al, 2021 ), working at concentrations commonly found in the plasma of cardiopathic patients treated with CGs ( López-Lázaro et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, S-Lea antigen can be carried in superfluity by a carbohydrate-rich protein, and it can be carried as ganglioside, one epitope per molecule extractable into a lipid fraction. We have previously reported partial purification of fucosylation and sialylation activities in the pathways to S-Lea biosynthesis in SW1116 cells (Jolif and Liepkalns, 1988;Liepkalns, 1990;Liepkalns and Larson, 1987;Liepkalns et al, 1988) using glycolipid acceptors.…”
mentioning
confidence: 99%